PENGARUH PELATIHAN TERHADAP PRESTASI KERJA KARYAWAN DI GRAND INNA HOTEL PADANG - atika prasuri (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2018)
Based on this study to determine the effect of training on employees work performance at Grand Inna Hotel Padang. This type of research_is causal associative. The sample used is total sampling, which is as many as 60 employees who are in the operational section, through a questionnaire with a Likert scale whose validity and reliability have been tested. The results obtained from this study are as follows: (1) training is in the very good category 68.33%, (2) employees work performance is in a very good category of 95%, (3) the results of testing a simple linear regression hypothesis obtained F for 8.649 with sig. 0.00 <0.05, then the training variable explains the variable employees performance of 13% and 87% influenced by other factors. Then the coefficient value of 0.248 is obtained with the value in sig. 0.00 <0.05. This means that each increase of 1 training unit will increase the 0.248 work achievement units of Grand Inna Hotel Padang employees. Keywords: Training, Employee Performance